RANCANGBANGUN PROGRAM APLIKASI TES KESEGARAN JASMANI INDONESIA BERBASIS ANDROID - Noveri Lysbetti Marpaung; Ridho Al Amzah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Indonesian Physical Fitness Test (TKJI) is a test to measure the physical fitness of someone during doing his/her daily activities without over tired. TKJI can be done to participants from 6 upto 19 years old. Implementation of TKJI manually makes Officers/Evaluators of TKJI have problems in assessing and calculating TKJI results based on number of participants. TKJI Evaluators also face problems when they want to review or compare test results of participants from the time before. Evaluator can not save the results of test on the site directly. On the other side, TKJI Participants cannot directly accept the results, but they must wait the results in the next few days, after test has been performed. Goal of the research is to make Application Software of TKJI based on Android for people 6 upto 19 years old to measure level of participant’s physical fitness and to make easier the assessing and calculating TKJI results. There are five criterias used, namely the 60 meter Test, Short Distance Running Test, Hanging Body Lift Test, Lying Down Test, Upright Jump Test, and the 1200 metre Medium Distance Running Test. The result of the test can be obtained by participants when they login to TKJI Application, each time after Evaluators uploaded the results. Blackbox testing result of this study toward 70 of interface displays based on 20 respondents gets 98.57%, which is categorized as Very Feasible by Category of Feasible System. Usability testing results produce 90.25% which is declared Very Feasible with same circumstances.